Short-term and long-term effectiveness of acupuncture and Tuina on knee osteoarthritis: study protocol for a randomized controlled trial - Zhao, Rui-li; Ma, Pei-hong; Liu, Bao-yan; Yu, Chang-he; Zhang, Hao-ran; Lv, Qian; Yang, Da-wei; Yang, Yu-ping; Liu, Hong-yan; Wang, Fu-yu; Yin, Chun-sheng; Su, Shao-guang; et al. (Frontiers in Neurology, 2023)
Background: Effectiveness of acupuncture and tuina in treating knee osteoarthritis (KOA) is still controversial, which limits their clinical application in practice. This study aims to evaluate the short-term and long-term effectiveness of acupuncture and tuina on KOA.Methods/design: This parallel-group, multicenter randomized clinical trial (RCT) will be conducted at the outpatient clinic of five Traditional Chinese Medicine hospitals in China. Three hundred and thirty participants with KOA will be randomly assigned to acupuncture, tuina or home-based exercise group with 1:1:1 ratio. The primary outcome is the proportion of participants achieving a minimal clinically important improvement, defined as a ≥12% reduction on the Western Ontario andMcMaster Universities Osteoarthritis Index (WOMAC) pain dimension on short-term (week 8) and long-term (week 26) compared with baseline. Secondary outcomes are knee joint conditions (pain, function and stiffness), self-efficacy of arthritis, quality of life, and psychological conditions, which will be evaluated by WOMAC score and the Patient Global Assessment (PGA), in addition, the respondents index of OMERACT-OARSI, Short Form 12 Health Survey(SF-12), arthritis self efficacy scale and European five-dimensional health scale(EQ-5D). Adverse events will be collected by self-reported questionnaires predefined.This study has been approved by the Ethics Committee of Beijing University of Chinese Medicine (2023BZYLL0708), and written informed consent will be obtained from all participants. Results will be disseminated through peer-reviewed publications and presented at scientific conferences. Protocol version: